ЭКОНОМИЧЕСКАЯ ИНТЕГРАЦИЯ И ЛИБЕРАЛИЗАЦИЯ МЕЖДУНАРОДНЫХ ЭКОНОМИЧЕСКИХ ОТНОШЕНИЙ - Бекмухаметова, А Б (Journal of Economic Research & Business Administration, 2015)
The achievement of mutually beneficial economic relations between the integrating countries should provide transition economies in the new organizational forms of cooperation, and liberalization of the movement of goods, services, capital and labor - to promote the implementation of priority joint projects in the manufacturing and processing industries.